Amalan perekrutan oleh firma di Malaysia : satu kajian empirikal - Tang, Swee Mei; Lim, Kong Teong (Universiti Utara Malaysia, 2004)
The objective of this research is to study current recruitment practices in Malaysia with particular reference to managerial jobs. The research also examines the level of personal knowledge and the extent of the company usage of recruitment techniques. Furthermore, this study also surveys the perception of human resource managers regarding the efectiveness of recruitment techniques in yielding high quality and high performing employees. Based on the average score, the findings reveal that respondents scored higher on knowledge than the company did on its usage. The results affirm the continuing popularity of traditionally used recruitment techniques such as newspaper advertisements, resumes and employee referrals.